Symptons of the contemporary world through the ethnographic mediation of literary journalism: notes on nonfiction narratives by David Foster Wallace - Coelho, Lilian Reichert (2014)
In this text I analyze three travel reports-essays-chronicles produced in the 1990s and in the beginning of the 21th Century by the north american writer David Foster Wallace as in between Literary Journalism and contemporary Sociology. The corpus is read from the idea of non-place, as developed by Augé (1994). As results, I point out that the writer on focus performing as journalist and ethnographer has captured some significant symptoms of the contemporary world.